Bleeding associated with acquired factor V inhibitor in a patient on warfarin treated successfully with prednisolone. (6th August 2013) - Khalafallah, Alhossain; Grabek, Julian; Hayes, Robert; Mohamed, Muhajir
Abstract : An 85-year-old man on warfarin for atrial fibrillation presented with skin bleeding. International normalised ratio (INR) and activated partial thromboplastin time (APTT) were elevated and did not correct even after warfarin reversal with vitamin K, prothrombin complex concentrate (PCC) and fresh frozen plasma. Mixing coagulation studies with normal plasma suggested the presence of an inhibitor rather than the multiple coagulation factor deficiencies expected with warfarin. Assays of the common-pathway coagulation factors revealed factor V concentration <2% with inhibitor level elevated to 11 Bethesda units. The bleeding resolved following a course of corticosteroids. Coagulation studies and factor V level returned to normal along with resolution of the inhibitor. We report the case of the diagnostic dilemma posed and successful therapy implemented despite the limited evidence-based data being available for the treatment of this rare condition.